Analysis of target mRNAs in the fixed-frozen human brain using a modified BaseScope-ISH Assay protocol - Owain Howell (STAR Protocols, 2022)
We describe a modified BaseScope™ Assay protocol (ACDBio) for RNA in situ hybridization on fixed-frozen human brain tissue. The original protocol caused tissue detachment due to harsh tissue pre-treatment. We therefore optimized it to improve tissue stability while providing high stain quality in fragile post-mortem tissue from aged donors with advanced neurodegeneration. The main changes include two additional fixation steps and modifications to the pre-treatment protocol. We also describe tissue imaging and stain quantification using the open-source QuPath software.